Determinant of Human Development Index in ASEAN Countries - A. Arisman (Signifikan: Jurnal Ilmu Ekonomi, 2018)
Human development index is one indicator of development progress on aspects of human quality in a country. This study aims to determine the factors that affect the human development index in nations in ASEAN member countries. The analysis technique used is regression by using panel data regression with fixed effect model. The results of processing with fixed effect model show that population and per capita income growth rate affects the human development index in ASEAN member countries, while the variable rate of inflation and unemployment rate does not have an impact on the human development index. This study implies the importance of government to control the population and acceleration of economic growth.DOI: 10.15408/sjie.v7i1.6756